Couples modernes – literarni par v srednjeevropskih modernističnih gibanjih - Magnone, Lena (Slavia Centralis, 2024)
The article reflects upon a specific phenomenon within Central European modernism: namely the couple composed of a New Woman and a Decadent. Focusing on Młoda Polska, Mlada Hrvatska, and Česká Moderna, the author presents three cases of literary couples: Stanisław Przybyszewski and Dagny Juel, Vladimir Jelovšek and Zofka Kveder, and Stanislav K. Neumann and Kamilla Neumannová. The findings prove that for a woman, to bond with a member of a literary movement was a way to gain access to the bohemian milieu and, more importantly, to the pages of the flagship magazines and, consequently, literary history.